2018
DOI: 10.2478/dim-2018-0007
|View full text |Cite
|
Sign up to set email alerts
|

Applications of inferential statistical methods in library and information science

Abstract: Research methods play an extremely important role in studies. Statistical methods are fundamental and vital for quantitative research. The authors of this paper investigated the research papers that used statistical methods including parametric inferential statistical methods, nonparametric inferential statistical methods, predictive statistical correlation methods, and predictive statistical regression methods in library and information science and examined the connections and interactions between statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
(38 reference statements)
1
11
0
Order By: Relevance
“…They reported t -test, chi-square, ANOVA as the most frequently used statistics. In a related study the same authors Zhang et al (2018) found significant relationship between statistical methods and application areas of studies performed. Kaur and Fink (2016) argue that advanced technologies such as machine learning and artificial intelligence are at experimental stage in HRM.…”
Section: Literature Reviewmentioning
confidence: 90%
See 1 more Smart Citation
“…They reported t -test, chi-square, ANOVA as the most frequently used statistics. In a related study the same authors Zhang et al (2018) found significant relationship between statistical methods and application areas of studies performed. Kaur and Fink (2016) argue that advanced technologies such as machine learning and artificial intelligence are at experimental stage in HRM.…”
Section: Literature Reviewmentioning
confidence: 90%
“…Medical field has robust and diversity of studies (Arnald et al, 2013;Nieminen et al, 2018) investigating the statistical models used in this field. Information and library science has a good number of studies (Zhang et al, 2016(Zhang et al, , 2018 exploring the use of statistics in the field. Statistical analyses can broadly be broken into two categories: confirmatory (CDA) and exploratory analysis (EDA).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of data analysis, the literature shows LIS scholars apply statistical methods in research (Ngulube, 2005b;Zhang et al, 2018); however, generally students have little knowledge on applying mathematical and statistical knowledge in research methodology (Daniel et al, 2018). In fact, in the last three decades, descriptive statistics has been predominantly used relative to inferential statistics (Ngulube, 2005b;Ullah and Ameen, 2018).…”
Section: Global Lis Research Methodology Trendsmentioning
confidence: 99%
“…Majority of the papers did not define hypotheses (80%), did not clearly state a significance level (80%), did not provide a complete set of statistical results (50%) and did not mention explicitly the statistical method (50%). Zhang et al. (2018) found that parametric inferential statistical methods were the most used methods 1,023 (34%) while the regression methods ( n = 377, 12%) were the least employed methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Inferential statistics explores differences or establishes association and causality among two or more variables. Inferential statistics can be divided into four categories including parametric, non-parametric, predictive correlation and predictive regression (Zhang et al. , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%